Aristotle on knowledge of nature and modern skepticism - Colaner, Nathan R. (Lexington Books, 2015)
Nathan R. Colaner articulates a notion of knowledge that is characteristically Aristotelian without being dependent on his metaphysics. Simultaneously, Colaner places Aristotle's epistemology in dialogue with modern thinkers' works to create a bridge between classical and modern philosophy.